MySRB and SRB - components of a Data Grid - Rajasekar, A.; Wan, M.; Moore, R. (11th International Symposium on High-Performance Distributed Computing (HPDC-11 2002), 2002)
Data Grids are becoming increasingly important in scientific communities for sharing large data collections and for archiving and disseminating them in a digital library framework. The Storage Resource Broker (SRB) provides transparent virtualized middleware for sharing data across distributed, heterogeneous data resources separated by different administrative and security domains. The MySRB is a Web-based interface to the SRB that provides a user-friendly interface to distributed collections brokered by the SRB. In this paper we briefly describe the use of the SRB infrastructure as tools in the data grid architecture for building distributed data collections, digital libraries, and persistent archives. We also provide details about the MySRB and its functionalities.